(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
The middle Cretaceous genus Paronastraea Beauvais, 1977 is being revised on the basis of sample material available from Italy, France, Germany, and Greece. Paronastraea, a plocoid and cerioid coral similar to Pachycoenia, is characterised by regular secondary septal apophyses arranged in pairs. Six species are distinguished by their respective numbers of septal cycles and systems, two of them in open nomenclature and one, Paronastraea occulta from the Early Aptian of Greece, is newly described. The genus occurred from the Barremian to the basal Cenomanian in the central and eastern Tethys.